2017
DOI: 10.1038/onc.2017.182
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miR16 in glioblastoma and glioblastoma stem cells: their correlation with proliferation, differentiation, metastasis and prognosis

Abstract: The function of miR16 in multiforme glioblastoma multiforme (GBM) and its stem cells (GSCs) remains elusive. To this end, we investigated the patterns of miR16 expression in these cells and their correlation with malignant behaviors and clinical outcomes. The levels of miR16 and its targeted genes in tumor tissue of GBM and GBM SGH44, U87, U251 cells as well as their stem cell counterparts were measured by qRT–PCR or western blot or immunohistochemistry. Luciferase reporter assay was used to confirm the bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 39 publications
1
26
1
Order By: Relevance
“…In TCGA data sets, we also addressed the question whether miR‐16‐5p expression is associated with overall survival of glioma patients. Expression of miR‐16‐5p was associated with overall survival in an institutional cohort of 132 glioblastoma patients . However, we found no prognostic role of high vs .…”
Section: Discussioncontrasting
confidence: 72%
See 4 more Smart Citations
“…In TCGA data sets, we also addressed the question whether miR‐16‐5p expression is associated with overall survival of glioma patients. Expression of miR‐16‐5p was associated with overall survival in an institutional cohort of 132 glioblastoma patients . However, we found no prognostic role of high vs .…”
Section: Discussioncontrasting
confidence: 72%
“…Following transient transfection of miR‐16‐5p precursor molecules into different glioma cell lines, we found reduced expression of each of these genes at the mRNA and/or protein levels. Previous studies had already shown that miR‐16‐5p directly binds the 3′‐UTR of CDK6 , CCND3 , CCNE1 , CDC25A and BCL2 [13,24–26,29,39,40,51,55,56]. Using 3′‐UTR luciferase reporter assays we confirmed its specific binding to the 3′‐UTR of WEE1 and CHEK1 .…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations